In vitro antiviral activity of penciclovir, a novel purine nucleoside, against duck hepatitis B virus. - Shaw, T (1994)
The in vitro antihepadnavirus activities of the purine nucleoside analogs ganciclovir (9-[2-hydroxy-1-(hydroxymethyl)ethoxymethyl]guanine) and penciclovir [9-(4-hydroxy-3-hydroxymethylbut-1-yl)guanine; BRL 39123] were compared in primary duck hepatocyte cultures congenitally infected with the duck hepatitis B virus (DHBV). Both compounds inhibited DHBV DNA replication to a comparable extent during continuous short-term treatment of the cultures. However penciclovir was more active both during longer-term continuous treatment (50% inhibitory concentrations: penciclovir, 0.7 +/- 0.1 microM; ganciclovir, 4.0 +/- 0.2 microM) and in washout experiments (50% inhibitory concentrations: penciclovir, 3.0 +/- 0.4 microM; ganciclovir, 46 +/- 1.5 microM) designed to compare the persistence of inhibitory activity after removal of the extracellular compound. The effects on viral protein synthesis were similar to the effects on viral DNA replication. These data suggest that penciclovir or its oral form, famciclovir, may have clinical utility in the treatment of chronic hepatitis B virus infection.